Evaluation of the efficacy of rotary and reciprocating systems for the removal of filling material for various root canal filling techniques - Neslihan Büşra Keskin; Selen İnce Yusufoğlu (Journal of Dental Research, Dental Clinics, Dental Prospects, 2023)
Background. This study aimed to evaluate the efficacy of various filling and retreatment techniques for oval-shaped root canals. Methods. Sixty distal roots of mandibular molar teeth were included in the study. The roots were prepared using the ProTaper Next (PTN) X4 rotary system and irrigation with 2.5% NaOCl. The roots were then divided into three groups and filled with Total Fill BC Sealer (FKG Dentaire) using three different techniques (n=20): single cone (SC), GuttaCore (GC), and warm vertical condensation (WVC). The retreatment procedure was performed using two different instrumentation techniques: Reciproc 50 (R50) and PTN X5 (n=10). To analyze the remaining filling material, the roots were divided buccolingually in two parts with the help of diamond separators, and photographs were taken at x16 magnification using a dental operating microscope (DOM). The ratio of the remaining filling materials was calculated using image analysis software and statistically evaluated using the Kruskal–Wallis test. Results. None of the assessed retreatment procedures completely removed the filling materials from the root canals. For both instrumentation techniques, more root canal filling material remained in the WVC group (P<0.05). Conclusion. The GC filling technique had a higher cleaning percentage than the WVC and SC techniques in the coronal region. The R50 system was found to be superior to the PTN X5 system for retreatment, and the root canal fillings applied using the WVC technique were more difficult to remove than the fillings applied using the other techniques.